From literary dissent to platform visibility: algorithmic circulation and the politics of contemporary Indonesian poetry - Muhamamad Faiz Ramadhan (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Contemporary Indonesian poetry increasingly circulates through digital platforms where literary dissent is shaped not only by textual form but also by visibility, shareability, comment infrastructures, and paratextual framing. Objective: This study examines how contemporary Indonesian poetry transforms dissent from a textual mode of critique into a platform-mediated public practice. Method: Using qualitative digital literary discourse analysis, this study analyses thirteen public poetry posts, five secondary scholarly sources, and three contextual sources through critical dissent discourse analysis, platform visibility mapping, and multimodal-paratextual semiotic analysis. Results: Findings show that poetic dissent is concentrated around state power, democracy, violence, memory, political economy, regional precarity, and bodily autonomy, but it is articulated through metaphor, satire, testimony, mourning, allegory, and symbolic indirection rather than direct ideological declaration. Findings also show that platform visibility is uneven: all poems are technically shareable, yet only some generate visible reader interaction or cross-platform traces. Implication: Moreover, editorial framing, authorial biography, regional markers, visual cues, and performance references shape how dissent becomes publicly readable. Novelty: The novelty of this study lies in reframing contemporary Indonesian poetry as mediated cultural action in which literary form, algorithmic circulation, and paratextual publicness jointly configure political meaning.